2016
DOI: 10.1038/leu.2016.176
|View full text |Cite
|
Sign up to set email alerts
|

A randomized phase III study of carfilzomib vs low-dose corticosteroids with optional cyclophosphamide in relapsed and refractory multiple myeloma (FOCUS)

Abstract: This randomized, phase III, open-label, multicenter study compared carfilzomib monotherapy against low-dose corticosteroids and optional cyclophosphamide in relapsed and refractory multiple myeloma (RRMM). Relapsed and refractory multiple myeloma patients were randomized (1:1) to receive carfilzomib (10-min intravenous infusion; 20 mg/m2 on days 1 and 2 of cycle 1; 27 mg/m2 thereafter) or a control regimen of low-dose corticosteroids (84 mg of dexamethasone or equivalent corticosteroid) with optional cyclophos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
94
1
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(108 citation statements)
references
References 23 publications
7
94
1
6
Order By: Relevance
“…37 However, another study showed that low-dose cyclophosphamide (50 mg daily) combined with steroids has markedly lower activity in lenalidomide-and bortezomib-exposed patients (63% of these patients were double-refractory to bortezomib and IMiDs), with at least PR in 11.4% of these patients and a median PFS and OS of only 3.3 months and 10.0 months, respectively. 38 This outcome is inferior to that observed with the REP regimen in doublerefractory MM patients and suggests clinical synergy between lenalidomide and low-dose cyclophosphamide.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…37 However, another study showed that low-dose cyclophosphamide (50 mg daily) combined with steroids has markedly lower activity in lenalidomide-and bortezomib-exposed patients (63% of these patients were double-refractory to bortezomib and IMiDs), with at least PR in 11.4% of these patients and a median PFS and OS of only 3.3 months and 10.0 months, respectively. 38 This outcome is inferior to that observed with the REP regimen in doublerefractory MM patients and suggests clinical synergy between lenalidomide and low-dose cyclophosphamide.…”
Section: Discussionmentioning
confidence: 47%
“…32 Carfilzomib monotherapy induces at least PR in 19.1% of extensively pretreated patients with a median PFS of 3.7 months. 38 Daratumumab induces at least PR in 29% to 36% of patients with a median PFS of 3.7 to 5.6 months, 45,46 whereas elotuzumab 47 has no single-agent activity in this setting. The outcome of the REP regimen also compares favorably to the results of carfilzomib-or pomalidomide-based combinations in relapsed/refractory For personal use only.…”
Section: Discussionmentioning
confidence: 99%
“…This CV safety analysis was based on phase 1/1b trials (PX-171-001, 18 26 (supplemental Figure 1). Eligibility criteria for phase 1 and 2 studies were presented previously.…”
Section: Methodsmentioning
confidence: 99%
“…Although monotherapy is not commonly used in patients with RRMM, it should be noted that bortezomib monotherapy has shown efficacy in the phase III APEX study (Table II) (Harrison et al, 2015;Richardson et al, 2005). However, carfilzomib monotherapy did not improve OS when compared with low-dose corticosteroid treatment (plus optional cyclophosphamide) in patients who had received ≥3 previous lines of therapy (Table 2) (Hajek et al, 2016). Currently there are no phase III trial data assessing the efficacy of ixazomib monotherapy.…”
Section: Treatment Options For Relapsed Diseasementioning
confidence: 99%